2007
DOI: 10.1007/s10549-006-9489-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the frequency and distribution of BRCA1 and BRCA2 mutations in breast/ovarian cancer cases from the Basque country with respect to the Spanish population: implications for genetic counselling

Abstract: The prevalence of unique and recurrent BRCA1 and BRCA2 pathogenic mutations and unclassified variants varies among different populations. Two hundred and thirty-six breast and/or ovarian cancer patients were analysed to clarify the role of these genes in the Basque Country. We also studied 130 healthy women from the general population from the same region. Fifteen different pathological mutations were found in 16 index cases: 10 truncating mutations, 4 missense mutations and 1 splicing mutation. c.3002_3003ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 27 publications
5
34
2
7
Order By: Relevance
“…We observed greater diversity and higher incidence for BRCA2 mutations than for BRCA1 (50.7% in BRCA2 vs. 41.9% in BRCA1) in correspondence with our previous reports [6], and with other studies performed in the Spanish population [14][15][16][17], but in disagreement with the other one [13]. We think that the larger incidence of mutations in BRCA2 could be a trait of the population of certain geographical areas of Spain, not related with the presence of the c.187_188delAG BRCA1 Ashkenazim mutation, as suggested by Infante et al [15], since in this study, we observed larger incidence of BRCA2 mutations in spite of having high incidence of this mutation.…”
Section: To the Editorsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed greater diversity and higher incidence for BRCA2 mutations than for BRCA1 (50.7% in BRCA2 vs. 41.9% in BRCA1) in correspondence with our previous reports [6], and with other studies performed in the Spanish population [14][15][16][17], but in disagreement with the other one [13]. We think that the larger incidence of mutations in BRCA2 could be a trait of the population of certain geographical areas of Spain, not related with the presence of the c.187_188delAG BRCA1 Ashkenazim mutation, as suggested by Infante et al [15], since in this study, we observed larger incidence of BRCA2 mutations in spite of having high incidence of this mutation.…”
Section: To the Editorsupporting
confidence: 92%
“…Eight of the mutations detected in BRCA1 were also observed in recent studies carried out in the Spanish population [13][14][15]. However, our results are not as concordant as those expected with the larger study carried out in the Spanish population [13].…”
Section: To the Editorcontrasting
confidence: 85%
See 1 more Smart Citation
“…1A; refs. [24][25][26]. Apart from the classic mutations of the donor and acceptor splice sites, two variants should be highlighted.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the results of BRCA1 and BRCA2 genetic testing previously reported in seven different areas of Spain: Galicia (North West) [5], Salamanca (West) [8], Castilla-León (North West-central) [9], Basque Country (North) [10], Aragón (North East) [11], Catalonia (North East-Mediterranean) [12], and Valencia (East) [13] ( Fig. 1).…”
Section: Methodsmentioning
confidence: 99%